2013
DOI: 10.1021/ja4114243
|View full text |Cite
|
Sign up to set email alerts
|

Isolable and Well-Defined Butadienyl Organocopper(I) Aggregates: Facile Synthesis, Structural Characterization, and Reaction Chemistry

Abstract: Four types of alkenyl organocopper(I) aggregates linked by 1,3-butadienyl and/or 1,3,5,7-octatetraenyl moieties were selectively realized in good isolated yields. All these organocopper(I) aggregates were structurally characterized by single-crystal X-ray structural analysis. These unprecedented aggregates, stabilized by multiple Cu-Cu interactions and the conjugated 1,3-butadienyl or 1,3,5,7-octatetraenyl bridges, could undergo controlled structural transformations. The 1,4-dicopper 1,3-butadienyl aggregate 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 82 publications
0
35
0
Order By: Relevance
“…9395 Fe Kβ X-ray emission spectroscopy (XES) analysis further demonstrates the presence of a carbide atom in the L-cluster, completing the stoichiometric definition of the L-cluster as an [Fe 8 S 9 C] cluster. 96 Together, these observations point to a novel synthetic route employed by NifB, one that couples/rearranges two [Fe 4 S 4 ] clusters into an [Fe 8 S 9 C] cluster concomitant with the radical SAM-dependent insertion of carbide and the addition of “the 9 th sulfur” (Figure 4B). …”
Section: The “Ex Situ” Biosynthesis Of M-clustermentioning
confidence: 91%
“…9395 Fe Kβ X-ray emission spectroscopy (XES) analysis further demonstrates the presence of a carbide atom in the L-cluster, completing the stoichiometric definition of the L-cluster as an [Fe 8 S 9 C] cluster. 96 Together, these observations point to a novel synthetic route employed by NifB, one that couples/rearranges two [Fe 4 S 4 ] clusters into an [Fe 8 S 9 C] cluster concomitant with the radical SAM-dependent insertion of carbide and the addition of “the 9 th sulfur” (Figure 4B). …”
Section: The “Ex Situ” Biosynthesis Of M-clustermentioning
confidence: 91%
“…Although neutral N,N-chelated spiro copper complexes are relatively common, the anionic C,N- or C,C-cheated spiro counterparts are sporadic. As mentioned above, Xi’s group found that the C,C-bidentate ligand is an excellent platform to build up diversified coordination complexes across the periodic table [ 32 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. The chelating effect increases the thermal stability of these organometallic species, facilitating isolation and following characterization.…”
Section: Mononuclear Organocopper Complexesmentioning
confidence: 99%
“…More recently, the trinuclear organocopper aggregate 15 has been obtained from 1,2,3,4‐tetra( n ‐propyl)‐1,4‐dilithio‐1,3‐butadien, CuCl, and LiI in 63 % yield . The 2e‐3c bond results in very short Cu⋅⋅⋅Cu distances [2.3749(8) and 2.4192(8) Å] and a bent geometry of the Cu I 3 chain [Cu out ⋅⋅⋅Cu in ⋅⋅⋅Cu out′ : 130.54(3)°].…”
Section: Linear Trinuclear Cui Complexesmentioning
confidence: 99%
“…More recently,t he trinuclearo rganocopper aggregate 15 has been obtainedf rom 1,2,3,4-tetra(n-propyl)-1,4-dilithio-1,3butadien, CuCl, and LiI in 63 %y ield. [29] [30] The monovalentc omplex cation contains an ideally linear chain of three Cu I centers (Cu out ···Cu in ···Cu out' :1 80.08)a nd intra-chain Cu I ···Cu I separations [2.6011(4) ]t hat are clearly below the sum of two copper van der Waals radii. [10]…”
Section: Neutral Trinuclear Cu I Complex Arraysmentioning
confidence: 99%